Ambiguous Genitalia: An Unexpected Diagnosis in a Newborn - Losa, Ana (2023)
Alterations in gonad formation or function can lead to congenital conditions in which chromosomal, gonadal, or anatomical sex is atypical. These conditions are referred to as disorders of sex development (DSD) and have a heterogeneous etiology. The assessment of these children by a multidisciplinary team is crucial for an accurate diagnosis and should be initiated promptly due to the potentially life-threatening nature of congenital adrenal hyperplasia, a common cause of DSD. We present a neonate born at 39 weeks with a weak cry, slight hypotonia, poor suction reflex, peculiar facies, and ambiguous genitalia. From the study carried out, the abdominopelvic ultrasound revealed a nodular structure compatible with the left gonad. Aneuploidy screening confirmed the presence of the Y chromosome. Additionally, normal endocrinological studies and the karyotype showed a genotype compatible with cri-du-chat syndrome with partial trisomy of chromosome 3. Children with cri-du-chat syndrome characteristically exhibit a cat-like cry and distinctive facial features, along with developmental delay and intellectual disability. Duplication of 3p is a rare genetic disorder, usually associated with other chromosomal anomalies and congenital malformations, namely, of the genitals